IPTEKS UNTUK LAYANAN KESEHATAN CUMA-CUMA (LKC) DOMPET DHUAFA PALEMBANG - Yosi Apriani; Wiwin A Oktaviani; Ade Arinia Rasyad (Aptekmas Jurnal Pengabdian pada Masyarakat, 2019)
From the results of the research that has been carried out a 220 watt DC to AC inverter circuit using AKI / battery has succeeded well according to the procedure. The working system of a DC inverter device is very useful for efficient use of electricity, especially in the application of medical devices at the Dompet Dhuafa (DD) Free Health Service (Palembang) in Palembang with a power of 220 watts. The working system of a 220 watt DC inverter circuit can convert DC voltage (direct voltage) to AC voltage (alternating voltage).